Absence of genotoxic effects of the chalcone (E)-1-(2-hydroxyphenyl)-3-(4-methylphenyl)-prop-2-en-1-one) and its potential chemoprevention against DNA damage using in vitro and in vivo assays - Lima, Débora Cristina da Silva; Vale, Camila Regina do; Véras, Jefferson Hollanda; Bernardes, Aline; Pérez, Caridad Noda; Chen-Chen, Lee (PLOS ONE, 2017)
The chalcone (E)-1-(2-hydroxyphenyl)-3-(4-methylphenyl)-prop-2-en-1-one), or 2HMC, displays antileishmanial, antimalarial, and antioxidant activities. The aim of this study was to investigate the cytotoxic, genotoxic, mutagenic, and protective effects of 2HMC using the Ames mutagenicity test, the mouse bone marrow micronucleus test, and the comet assay in mice. In the assessment using the Ames test, 2HMC did not increase the number of His+ revertants in Salmonella typhimurium strains, demonstrating lack of mutagenicity. 2HMC showed no significant increase in micronucleated polychromatic erythrocyte frequency (MNPCE) in the micronucleus test, or in DNA strand breaks using the comet assay, evidencing absence of genotoxicity. Regarding cytotoxicity, 2HMC exhibited moderate cytotoxicity in mouse bone marrow cells by micronucleus test. 2HMC showed antimutagenic action in co-administration with the positive controls, sodium azide (SA) and 4-nitroquinoline-1-oxide (4NQO), in the Ames test. Co-administered and mainly pre-administered with cyclophosphamide (CPA), 2HMC caused a decrease in the frequency of MNPCE using the micronucleus test and in DNA strand breaks using the comet assay. Thus, 2HMC exhibited antimutagenic and antigenotoxic effects, displaying a DNA-protective effect against CPA, SA, and 4NQO carcinogens. In conclusion, 2HMC presented antimutagenic, antigenotoxic and moderate cytotoxic effects; therefore it is a promising molecule for cancer prevention.